Optimizing the vehicle routing problem using the saving matrix method for LPG gas cylinder distribution routes PSO (case study : PT. Sukma Abadi in Cilacap Regency) - Retno Ambar Fiyanti (Unnes Journal of Mathematics, 2023)
This study aims to determine the distribution route using the saving matrix method which will then be sorted using the nearest neighbor, nearest insert, and farthest insert methods. Sorting routes using the nearest neighbor, nearest insert, and farthest insert methods is calculated manually, then the effectiveness of using the three sorting methods is compared. Data collection was carried out by direct observation and interviews and using Google maps to find the distance from the depot to the base. From this study, it was found that the nearest neighbor and nearest insert method produced the same results and were more effective than the farthset insert method. The nearest neighbor or nearest insert method can optimize the distance by 16.46% and distribution costs can be reduced by 2.42% from conditions without optimization calculations. Thus it can be concluded that the nearest neighbor or nearest insert method can be used as an alternative for determining the distribution route for LPG gas cylinders by PT. Sukma Abadi, Cilacap Regency.